A gene signature to predict high tumor-infiltrating lymphocytes after neoadjuvant chemotherapy and outcome in patients with triple-negative breast cancer. (25th October 2017) - Criscitiello, C; Bayar, M A; Curigliano, G; Symmans, F W; Desmedt, C; Bonnefoi, H; Sinn, B; Pruneri, G; Vicier, C; Pierga, J Y; Denkert, C; Loibl, S; et al.
Abstract: Background: In patients with triple-negative breast cancer (TNBC), the extent of tumor-infiltrating lymphocytes (TILs) in the residual disease after neoadjuvant chemotherapy (NACT) is associated with better prognosis. Our objective was to develop a gene signature from pretreatment samples to predict the extent of TILs after NACT and then to test its prognostic value on survival. Patients and methods: Using 99 pretreatment samples, we generated a four-gene signature associated with high post-NACT TILs. Prognostic value of the signature on distant relapse-free survival (DRFS) was first assessed on the training set ( n   =  99) and then on an independent validation set ( n   =  115). Results: A four-gene signature combining the expression levels of HLF, CXCL13, SULT1E1, and GBP1 was developed in baseline samples to predict the extent of lymphocytic infiltration after NACT. In a multivariate analysis performed on the training set, this signature was associated with DRFS [hazard ratio (HR): 0.28, for a one-unit increase in the value of the four-gene signature, 95% confidence interval (CI): 0.13–0.63)]. In a multivariate analysis performed on an independent validation set, the four-gene signature was significantly associated with DRFS (HR: 0.17, 95% CI: 0.06–0.43). The four-gene signature added significant prognostic information when compared with the clinicopathologic pretreatment model (likelihood ratio test in the training set P   =  0.004 and in the validation set P   =  0.002). Conclusions: A four-gene signature predicts high levels of TILs after anthracycline-containing NACT and outcome in patients with TNBC and adds prognostic information to a clinicopathological model at diagnosis.